Changes in health‐related quality of life with long‐term eltrombopag treatment in adults with persistent/chronic immune thrombocytopenia: Findings from the EXTEND study. Issue 2 (29th November 2018) - Khelif, Abderrahim; Saleh, Mansoor N.; Salama, Abdulgabar; Portella, Maria do Socorro O.; Duh, Mei Sheng; Ivanova, Jasmina; Grotzinger, Kelly; Roy, Anuja N.; Bussel, James B.
Abstract: Patients with persistent/chronic immune thrombocytopenia (cITP) have low platelet counts, increased risk of bleeding and bruising, and often suffer from reduced health‐related quality of life (HRQoL). cITP treatments may either improve HRQoL by increasing platelet counts or decrease it because of side effects. The open‐label EXTEND study (June 2006 to July 2015) evaluated long‐term safety, tolerability, and efficacy of eltrombopag (an oral thrombopoietin‐receptor‐agonist) in adults with cITP who completed a previous eltrombopag ITP trial. The final results of EXTEND were published and used to assess changes in patient‐reported HRQoL over time and association between HRQoL and platelet response. Four validated HRQoL instruments were administered: SF‐36v2 including physical component summary (PCS) and Mental Component Summary; Motivation and Energy Inventory Short Form (MEI‐SF); Fatigue Subscale of FACIT (FACIT‐Fatigue); and FACT‐Thrombocytopenia Subscale Six‐Item Extract (FACT‐Th6). For the 302 patients enrolled, median duration of eltrombopag treatment was 2.37 years. All 4 HRQoL instruments demonstrated positive mean changes from baseline over time adjusted for patient baseline characteristics and rescue therapy use, and had positive association with platelet response (platelet count ≥30 × 10 9 /L; ≥50 × 10 9 /L; and ≥50 × 10 9 /L and >2 times baseline). Improvements from baseline started within 3 months and persisted through 5 years of treatment for FACIT‐Fatigue and FACT‐Th6 ( P <.05 for nearly all time points); through 2.5 years for SF‐36v2 PCS and less consistently for the MEI‐SF. In conclusion, in addition to eltrombopag increasing platelet counts and reducing bleeding/bruising, it also alleviated fatigue, concerns about bleeding and bruising, and improved physical function in many patients, especially responders.